From a seed to a harvest Wiremu St Chapel 1921-1996 - Swallow, Frederick; Wiremu Street Chapel (Auckland, NZ Wiremu Street Chapel (Christian Brethren), 1996)
Includes personal stories, photographs and recipes.
Keywords: Brethren movement -- History -- New Zealand